“Dosis de Fertilizante con microorganismos eficientes (ferti em) en el rendimiento del cultivo de cebolla china (allium fistolosum) variedad roja chiclayana-distrito de Lamas” - Linares Bensimon, Alfonso (2015)
The present research had as general objective to determine the dose of organic fertilizar enriched with beneficia! microorganisms (Ferti EM) with greater effect for the production of Chinese onion (Allium fistolosum) and specific objectives: To evaluate four doses of organic fertilizar enriched with beneficia! microorganisms (EM Ferti) in Chinese culture (fistolosum Allium) onion (var. chiclayana red), in the district of Lamas and perform economic analysis of the treatments under study. This research was performed in fundo "PACIFIC" located in the District of Lamas, Lamas province, San Martin Department - Peru. The experimental design applied was the statistical design of randomized complete block (RCBD) with four blocks, five treatments and whose processing field data were processed using the SPSS . 19 program which uses the P-value as a statistical comparison to levels 0.01 and 0.05 confidence for the analysis of variance and multiple range test of Duncan at P <0.05. The treatments were 0.4, 0.6, 0.8 and 1.0 Tn.ha Ferti EM-1, also considerad an absoluta control. The results determinad that the dose of organic fertilizar enriched with beneficia! microorganisms (EM FERTI) with better agronomic and economic results for the production of Chinase onion (Allium fistolosum) was adose 1.0 Tn.ha Ferti EM-1, resulting in a performance of 26166. 7 kg ha-1 and a net income of S l. 1528.35 nuevos soles and the increase every 0.2 Tn.ha Ferti EM-1 (independent variable) develop positiva linear responses on the dependent variables (diameter of the neck of the plant, bulb diameter and length of the floor) Keywords: beneficia! microorganisms, green onion, fertilizar rate